Enhancing English Reading Skills through ChatGPT-OpenAI: A Study on Vocational High School Students - Muman Muman (Jurnal Pemberdayaan Masyarakat, 2025)
In the rapidly evolving landscape of education, the integration of artificial intelligence has opened new doors to more engaging and personalized learning experiences. Hence, the objectives of this research are to examine the famous application called as ChatGPT-OpenAI whether this application can develop students’ reading skill. The researcher used classroom action reach method to collect and analyse the data. The cycles of this method are planning, acting, observing, and reflecting with the procedure of planning, problem identification, implementation of action, observation, reflection, revision, next action cycle, documentation, data analysis and findings, and conclusion and recommendation. The result of implementing ChatGPT-OpenAI to enhance English reading skills among vocational high school students gives the rapid advancements in artificial intelligence. ChatGPT offers an interactive and engaging learning experience, particularly in improving students' comprehension of descriptive texts. For utilizing classroom action research, it measures the effectiveness of ChatGPT-OpenAI through pre-tests, post-tests, and student feedback. The findings indicate a significant improvement in reading abilities, with students demonstrating enhanced comprehension and engagement. The results suggest that ChatGPT-OpenAI is a valuable educational tool for fostering English reading proficiency in vocational school. This finding means teacher should be aware of nowadays is 21th era, so ChatGPT-OpenAI is apart of them which has to be mastered by teachers in developing students’ reading skill.